PERUBAHAN DAN KERENTANAN PENGHIDUPAN RUMAH TANGGA NELAYAN BERBASIS PERIKANAN TERUBUK DI KABUPATEN BENGKALIS PROVINSI RIAU - Afrizal Afrizal; Zulkarnaini Zulkarnaini; Victor Amrifo (Berkala Perikanan Terubuk, 2018)
The objective of this research is to collect fishery based household livelihood vulnerability database, to know government efforts in reducing the vulnerability and to maintain the sustainability of fisherman's livelihoods based on terubuk. The research method is conducted qualitatively by involving informants directly or indirectly with fishing activities and fishery business terubuk. The results showed that the change of livelihood of fisherman fishery-based fishermen was caused by environmental change either from ecological asphek or from social culture asfek. Being a fisherman is a derivative work of the ancestors, the sources of vulnerability that occurs not only from natural capital (fish terubuk) but also socially, economically, and politically, the vulnerabilities of fishery-based fishery-based households are initially shaky. This vulnerability is a seasonal trend and is a habit for fishermen.